Large eddy simulation of density current on sloping beds. (May 2018) - Chawdhary, Saurabh; Khosronejad, Ali; Christodoulou, George; Sotiropoulos, Fotis
Highlights: Numerical simulation of density current fronts down a slope. Comparison with experiments and power law of plume spreading. Two different conditions studied involving different slopes and buoyancy. Effect of buoyancy studied on a stratified jet. Abstract: We carry out high-resolution large-eddy simulation (LES) of stratified flows developing as dense underflows over two different bed slopes of 5 ° and 15 ° in an laboratory-scale tank. Simulations for the corresponding unstratified flows are also carried out to help elucidate the effects of stratification on the dynamics of the flow and overall evolution of the effluent front. The simulated density current flows have also been investigated experimentally by continuously releasing down a sloping plane a fluid that is slightly denser than the ambient fluid. The Navier Stokes equations with the Boussinesq approximation, to account for the stratification due to density difference, are solved numerically using a second-order accurate finite-difference method (Khosronejad and Sotiropoulos, 2014). The simulated structure of the density currents at quasi-equilibrium are shown to be in reasonable agreement with the experimental observations. The variation of the half-width of the density current plume with downstream length is shown to exhibit different power law regimes on a log scale. Spectral analysis reveal existence of large scale structures in the flow. Comparative analysis of the dynamics of the coherent structures in the stratified and non-stratified flows reveal that stratification has a profound effect on the large-scale features of the flow.